2016
DOI: 10.1038/ncomms12570
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of jasmonate and phytochrome B signalling uncouples plant growth-defense tradeoffs

Abstract: Plants resist infection and herbivory with innate immune responses that are often associated with reduced growth. Despite the importance of growth-defense tradeoffs in shaping plant productivity in natural and agricultural ecosystems, the molecular mechanisms that link growth and immunity are poorly understood. Here, we demonstrate that growth-defense tradeoffs mediated by the hormone jasmonate are uncoupled in an Arabidopsis mutant (jazQ phyB) lacking a quintet of Jasmonate ZIM-domain transcriptional represso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
392
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(409 citation statements)
references
References 70 publications
(113 reference statements)
16
392
1
Order By: Relevance
“…We show here that G. robertianum, which occurs in forest understories, enhances its immunity against the fungal pathogen B. cinerea upon shade detection, rather than the reduced immunity observed in shade avoiding Arabidopsis and G. pyrenaicum. The mechanism through which low R:FR reduces pathogen resistance in shade-intolerant plants is not yet fully established but involves upregulation of the JAZ proteins, which are negative regulators of the JA pathway (Moreno et al, 2009;Cerrudo et al, 2012;Campos et al, 2016). Indeed, the Geranium ortholog of JAZ3 (OMCL7907) is induced by low R:FR in the evening in G. pyrenaicum, but not in G. robertianum ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…We show here that G. robertianum, which occurs in forest understories, enhances its immunity against the fungal pathogen B. cinerea upon shade detection, rather than the reduced immunity observed in shade avoiding Arabidopsis and G. pyrenaicum. The mechanism through which low R:FR reduces pathogen resistance in shade-intolerant plants is not yet fully established but involves upregulation of the JAZ proteins, which are negative regulators of the JA pathway (Moreno et al, 2009;Cerrudo et al, 2012;Campos et al, 2016). Indeed, the Geranium ortholog of JAZ3 (OMCL7907) is induced by low R:FR in the evening in G. pyrenaicum, but not in G. robertianum ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some evidence in the literature indicating that growth and defense can be regulated simultaneously (Francisco et al, 2016;Campos et al, 2016;de Wit et al, 2013), much of the research done in the area of growth and immunity has shown that activation of plant defense responses requires a major reallocation of resources away from growth to immunity (Huot et al, 2014). Consequently, plants must tightly regulate and fine-tune the signals that control this trade-off.…”
mentioning
confidence: 99%
“…The clearest examples of these trade-offs are constitutive defense mutants in which growth is severely hindered [45][46][47][48][49][50]. Photosynthesis is often reported to be decreased during defense responses, which would reduce growth and biomass if resources are limiting [51,52].…”
Section: Plant Immunity Constrains Growth and Developmentmentioning
confidence: 99%
“…Chlorophyll degradation itself may be a defensive strategy, as degradation products have anti-insect activity [56]. Other studies have shown that photosynthetic rates are not perturbed when defense responses are activated in the absence of physical damage, suggesting that some reports of decreased photosynthesis could be a consequence of physical damage (e.g., localized water loss from disrupted cells) [48,49,57]. Importantly, active defense responses trigger reduced growth without a corresponding reduction in photosynthesis, demonstrating that decreased photosynthesis is not the main cause of reduced growth during defense responses [48,49].…”
Section: Plant Immunity Constrains Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation